Immunogenicity and protective efficacy of an RSV G S177Q central conserved domain nanoparticle vaccine - Bergeron, Harrison C.; Murray, Jackelyn; Juarez, Maria G.; Nangle, Samuel J.; DuBois, Rebecca M.; Tripp, Ralph A. (Frontiers in Immunology, 2023)
Respiratory syncytial virus (RSV) can cause lower respiratory tract disease in infants and elderly populations. Despite decades of research, there remains no safe and approved RSV vaccine. Previously, we showed that an RSV G glycoprotein subunit vaccine candidate with a single point mutation within the central conserved domain (CCD), i.e. S177Q, considerably improved immunogenicity. Here, we examine the development of nanoparticle (NP) vaccines having either an RSV G protein CCD with wild-type sequence (NP-WT) or an S177Q mutation (NP-S177Q). The NP vaccine immunogens were adjuvanted with monophosphoryl lipid A (MPLA), a TLR4 agonist to improve Th1-type responses. BALB/c mice were primed with 10 µg of NP-WT vaccine, NP-S177Q, or vehicle, rested, and then boosted with a high (25 µg) or low (10 µg) dose of the NP-WT or NP-S177Q homologous candidate and subsequently challenged with RSV A2. The results showed that mice boosted with NP-S177Q developed superior immunogenicity and neutralizing antibodies compared to NP-WT boosting. IgG from either NP-S177Q or NP-WT vaccinated mice did not interfere with fractalkine (CX3CL1) binding to CX3CR1 and effectively blocked G protein CX3C-CX3CR1 binding. Both NP-WT and NP-S177Q vaccination induced similar neutralizing antibodies to RSV in challenged mice compared to vehicle control. NP-S177Q boosting improved correlates of protection including reduced BAL cell infiltration following RSV challenge. However, the NP vaccine platform will require improvement due to the poor solubility and the unexpectedly weaker Th1-type IgG2a response. The results from this study support further NP-S177Q vaccine candidate development.